2016
DOI: 10.3346/jkms.2016.31.10.1595
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Trunk Body Composition and Spinal Bone Mineral Density in Korean Males versus Females: a Farmers' Cohort for Agricultural Work-Related Musculoskeletal Disorders (FARM) Study

Abstract: The purpose of this study was proposed to identify the association of trunk body composition with spinal bone mineral density (BMD) in Korean male and female farmers. A total of 523 Korean farmers (259 males, 44 premenopausal females, and 220 postmenopausal females) were recruited. Computed tomography scans were acquired at the mid-L4 vertebral level, and total trunk muscle mass (TMM, cm3), back muscle mass (BMM), and abdominal wall muscle mass (AMM), total trunk fat mass (TFM), visceral fat mass (VFM), and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…The results of our study further demonstrate the positive association between weight and bone mass. Consistent with our findings, the majority of previous studies involving adults [27,[39][40][41][42][43] or children [44] revealed a positive correlation between FM and BMD/BMC without controlling for body weight. However, after we statistically removed the mechanical loading effect of body weight, we observed significant inverse relationships between various body fat measures and bone mineral status indices.…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study further demonstrate the positive association between weight and bone mass. Consistent with our findings, the majority of previous studies involving adults [27,[39][40][41][42][43] or children [44] revealed a positive correlation between FM and BMD/BMC without controlling for body weight. However, after we statistically removed the mechanical loading effect of body weight, we observed significant inverse relationships between various body fat measures and bone mineral status indices.…”
Section: Discussionsupporting
confidence: 92%
“…Site-specific differences were found in the effects of fat and muscle mass on BMD. Kang et al [ 15 ] found that the increase in trunk fat mass was positively correlated with spinal bone mineral density, which was beneficial to local lumbar BMD. Also, some studies showed that visceral fat and spinal bone marrow fat accumulation were disadvantageous to spinal BMD and reduced abdominal fat was good for bone health [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…People with reduced muscle mass and obesity have a higher risk of fractures compared with people who are simply obese [ 13 ]. The results of the correlation between fat and bone density in different parts are inconsistent [ 14 , 15 ], and the association between fat and bone is affected by age, sex, and fat location [ 16 ]. The weight change in patients with T2DM is also accompanied by changes in fat, muscle mass and its distribution, and mass composition ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen influences many aspects of adiposity, including the volume and regional distribution of adipose tissue, as well as pathophysiological changes specific to adipose depot sites [ 65 ]. Generally speaking, estrogens are associated with a more favorable lipid profile compared to androgens [ 66 ]. Thus, the decline of estrogen combined with the increase in relative androgens may be mechanistically related to the adverse lipid profile seen during the menopause.…”
Section: The Menopause Increases the Risk Of Metabolic Disordersmentioning
confidence: 99%